Telling Apart Motor Noise and Exploratory Behavior, in Early Development - Gliga, Teodora (Frontiers in Psychology, 2018)
Infants’ minutes long babbling bouts or repetitive reaching for or mouthing of whatever they can get their hands on gives very much the impression of active exploration, a building block for early learning. But how can we tell apart active exploration from the activity of an immature motor system, attempting but failing to achieve goal directed behavior? I will focus here on evidence that infants increase motor activity and variability when faced with opportunities to gather new information (about their own bodies or the world) and propose this as a guiding principle for separating variability generated for exploration from noise. I will discuss mechanisms generating movement variability, and suggests that, in the various forms it takes, from deliberate hypothesis testing to increasing environmental variability, it could be exploited for learning. However, understanding how variability in motor acts contributes to early learning will require more in-depth investigations of both the nature of and the contextual modulation of this variability.